European extreme precipitation: The effects of spatio-temporal resolution of the data - Hamouda M. E.; Pasquero C. (Weather and Climate Extremes, 2021)
European wintertime precipitation is known to be skilfully estimated in reanalysis data and model simulations since it is highly correlated with large scale, low frequency modes of variability, namely the North Atlantic Oscillation (NAO). Since the NAO is mainly a wintertime mode of variability, the skill of estimating precipitation becomes more limited in other seasons, most importantly in summer, when precipitation is mainly a result of mesoscale convection. In this study, we use the Weather Research and Forecast (WRF) model, to show the added value of using a high resolution, convection-permitting model to estimate precipitation extremes. The results show that WRF succeeds to correct the failure of ERA-Interim reanalysis to capture the positive trends over the last decades of European extreme precipitation in summer and transition seasons, that are indicated by observational data (E-OBS) and previous literature. Partial improvements are evident using ERA5 reanalysis, specifically in Spring and in Autumn. In winter, changes in European extreme precipitation over the last decades are dominated by variations in the NAO index, and are well reproduced both in reanalysis data and in the high resolution WRF downscaling.